"Ectrogella" Parasitoids of the Diatom Licmophora sp. are Polyphyletic. (24th July 2019) - Garvetto, Andrea; Perrineau, Marie‐Mathilde; Dressler‐Allame, Melina; Bresnan, Eileen; Gachon, Claire M. M.
Abstract: The diatom genera Licmophora and Fragilaria are frequent epiphytes on marine macroalgae and can be infected by intracellular parasitoids traditionally assigned to the oomycete genus Ectrogella . Much debate and uncertainty remains about the taxonomy of these oomycetes, not least due to their morphological and developmental plasticity. Here, we used single‐cell techniques to obtain partial sequences of the parasitoids 18S and cox2 genes. The former falls into two recently identified clades of Pseudo‐nitzschia parasites temporarily named OOM_1_2 and OOM_2, closely related to the genera of brown and red algal pathogens Anisolpidium and Olpidiopsis . A third group of sequences falls at the base of the red algal parasites assigned to Olpidiopsis . In one instance, two oomycete parasitoids seemed to co‐exist in a single diatom cell; this co‐occurrence of distinct parasitoid taxa not only within a population of diatom epiphytes, but also within the same host cell, possibly explains the ongoing confusion in the taxonomy of these parasitoids. We demonstrate the polyphyly of Licmophora parasitoids previously assigned to Ectrogella (sensu Sparrow, 1960) and show that parasites of red algae assigned to the genus Olpidiopsis are most likely not monophyletic. We conclude that combining single‐cell microscopy and molecular methods is necessary for their full characterisation.